(untitled) (Journal of Dhaka National Medical College & Hospital, 2025)
Background: The ethanolic extract of green tea is believed to significantly reduce lipid levels in rats with experimentally induced hypercholesterolemia. Objectives: To determine the lipid-lowering efficacy of green tea in rats with experimentally induced hyperlipidemia. Materials and Methods: An experimental study was done to determine the hypocholesterolaemic impact of green tea (Camellia sinensis) on rats with induced hypercholesterolaemia. The study was carried out from July 2015 to June 2016 in the Department of Pharmacology & Therapeutics at Dhaka Medical College, Dhaka. This study comprised 42 healthy rats of the Norwegian strain, divided into 6 groups. Atorvastatin served as the reference medication for comparison. Rats were administered a fatty meal consisting of 1.5 cc of olive oil and 1% cholesterol to induce hypercholesterolemia. The experimental group was administered ethanolic extract of green tea at dosages of 100 mg/kg and 200 mg/kg. Each group was treated for ten days and subsequently sacrificed on the eleventh day. The serum low-density lipoprotein (LDL) level was assessed with lipid profile kits. Result: The serum LDL levels in the groups of rats administered 100 mg/kg and 200 mg/kg of ethanolic extract of green tea, together with a 1% cholesterol diet, were lower than those in the hypercholesterolemic control group. The decrease in LDL levels was comparable to that observed in hypercholesterolemic rats administered 0.14 mg/kg atorvastatin for 10 days. The mean serum LDL levels, along with their standard deviations, for groups C, D, E, and F were recorded as 82.81 ± 2.28, 60.68 ± 3.28, 32.6 ± 3.12, and 30.88 ± 3.93 mg/dl, respectively. All groups exhibited a reduction in serum LDL levels when compared to the hyperlipidemic control group (group C). However, changes were markedly significant in groups E and F (p<0.001, p<0.001) (Table V, Fig. 5.5). Conclusion: Green tea (camelia sinesis) exhibits significantly hypolipidemic effect. Several double blinded randomized controlled clinical trial should be done after careful toxicology study. Then it could be act as a potent hypolipidaemic agent for therapeutic use. J. Dhaka National Med. Coll. Hos. 2025; 31 (01): 25-28